Exploring the associations between behavioral health risk factors, abnormal eating attitudes and socio-demographic factors among Chinese youth: Survey of 7,984 vocational high school students in Hunan in 2020 - Liu, Jieyu; Teng, Ziwei; Chen, Zirong; Wei, Zirou; Zou, Tianxiang; Qin, Yue; Yuan, Hui; Liu, Minghui; Chen, Jindong; Tang, Hui; Xiang, Hui; Wu, Haishan; et al. (Frontiers in Psychiatry, 2022)
Background: This study investigated the associations between behavioral health risk factors (anxiety, depression, stress, insomnia, drinking, smoking) and abnormal eating attitudes among Chinese vocational high school students (CVHSS). Potential moderating relationships were also explored with relevant socio-demographic factors of the student’s age, sex, rural or urban community, household income, family type and educational level of the father and mother. Methods: This study investigated the associations between behavioral health risk factors (anxiety, depression, stress, insomnia, drinking, smoking) and abnormal eating attitudes among Chinese vocational high school students (CVHSS). Potential moderating relationships were also explored with relevant socio-demographic factors of the student’s age, sex, rural or urban community, household income, family type and educational level of the father and mother. Results: The prevalence rates for behavioral health problems among these students ranged widely depending on the risk factor: 42.5% insomnia, 41.3% anxiety, 26.2% depression, 14.4% stress, 13.7% drinking, and 8.3% smoking. Additionally, 61.7% of students were at-risk for at least one of these six behavioral health disorders. Abnormal eating attitudes were associated with depression (r = .422), anxiety (r = .490), stress (r = .490), and insomnia (r = .375), with all of these relationships being significant (p < .01) and large size statistical effects. However, other analyses found that none of the socio-demographic background factors had meaningful associations with the behavioral health risk factors (0 of 28 tests) and very few background factors were associated with the abnormal eating attitude measures (only 3 of 35 tests). Females had higher levels than males on dieting and bulimia but not on the other two eating attitude components. Conclusions: This study determined that behavioral health risk factors (sleep problems and anxiety in particular) were common among high school students in China and that mental health and sleep disorder risks also tended to co-occur in some students with abnormal eating attitudes. Therefore, prevention and early identification programs for behavioral risk factors are needed for this population. It is important to pay more attention to students with abnormal eating attitude-related symptoms, who may have also underlying mental health problems and need further evaluation.